Pengembangan Perangkat Pembelajaran Fisika Menggunakan Model Siklus Belajar 5E untuk Melatihkan Kemampuan Berpikir Kritis - Armansyah Armansyah; Muslimin Ibrahim; Wasis Wasis (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
The objective of this reaserch was to produce physics learning materials with learning cycles (5E) model which focuced on the validity, practically, and effectiveness to facilitate student’s critical thinking ability in calor matter. The learning tools development using 4D (define, design, develop, and disseminate)  development model and have been tested on second semester students of physics education, The Science Teacher Training Institute of Mataram. This trial development of research using one group Pre-test Post-test Design. Data collection methods used were validation paper questionnaires, tests and observation, whereas data analysis techniques using qualitative and quantitative descriptive method. Based on the assessment the validator has a valid criteria, showing several findings, namely, 1) the devices at the implementation stage, devices are developed have  practical criteria, which are measured by the implementation of the criteria learning “well done” and the response of students are “strong” 2) the effective developed  to train critical thinking ability, where there is an increase in students, critical thinking ability from the initial test on 62 to 90 in the final test. The result of the study generally show that physics learning devices use a valid, practical, and effective, and 5E learning cycle model to train students critical thingking ability.